PERANCANGAN RADIO FREQUENCY IDENTIFICATION (RFID) PADA TRANSAKSI PEMINJAMAN DAN PENGEMBALIAN BUKU DI PERPUSTAKAAN (Jurnal Edik Informatika Penelitian Bidang Komputer Sains dan Pendidikan Informatika, 2022)
Radio frequency identification or better known as RFID is a method of identification of objects that use radio waves. The process of identification by RFID Reader and RFID Transponder (RFID Tag). An RFID tag is attached to an object or an object to be identified. Each RFID tag has a unique identification number data, so no RFID tag has the same ID number. RFID Reader reads the ID number contained in the RFID tag so that the object or object can be identified. Radio frequency identification (RFID) applications have been widely developed. One of the RFID developed here is as a Transaction on Lending and Returning Books in a library with a Web system. The system is made easier for admins to carry out the lending process and the return transaction process because every transaction process that occurs is stored in the database.